Rescue Inventory and Turtle Rehabilitation at the Turtle Education and Conservation Center Denpasar-Bali - Ni Kadek Dwi Agustini; Sang Ayu Made Putri Suryani; I Wayan Arya; Yoga Parawangsa (East Asian Journal of Multidisciplinary Research, 2023)
Turtles are ancient animal species that have survived millions of years ago until today. The turtle population in Indonesia is currently facing various threats to its sustainability. This study aims to determine the number of stranded turtles and the results of confiscation in the 2018-2023 period and to determine the condition of the turtles after being rescued by TCEC. This research was conducted on January 9 - February 11 at the Turtle Conservation and Education Center. Samples were all types of turtles that were rescued from early 2018-2023 by the TCEC and were rehabilitated in the ponds that had been provided. The results of this study indicate that in 2020 there was an increase in rescue cases carried out by the TCEC. The factor for the surge in rescues in 2020 was due to bad weather which stranded turtles, apart from that there were strong winds, heavy ocean currents, and fishing activities from the community that at that time were affected by Covid-19, all people switched professions to become fishermen which caused a surge in rescue cases with the statement bycatch in 2020.